2006
DOI: 10.1007/s00239-005-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genome Dynamics in Plants and Animals: Convergent Gene Fusions of a MutS Homologue

Abstract: Mitochondrial processes influence a broad spectrum of physiological and developmental events in higher eukaryotes, and their aberrant function can lead to several familiar disease phenotypes in mammals. In plants, mitochondrial genes directly influence pollen development and the occurrence of male sterility in natural plant populations. Likewise, in animal systems evidence accumulates to suggest important mitochondrial functions in spermatogenesis and reproduction. Here we present evidence for a convergent gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 30 publications
1
82
0
Order By: Relevance
“…While both genes have maintained sequence features strongly reminiscent of their bacterial counterparts, several modifications have occurred in both genes that appear to be conserved in plants. We have described some of the distinguishing features of the RECA3 protein sequence in this study and recently reported novel features of MSH1, including well-conserved protein domains and an unusual fusion with a GIY-YIG endonuclease (Abdelnoor et al, 2006). Other essential recombination controls within the mitochondrial and plastid genomes appear to be performed by at least two additional recA homologs in Arabidopsis.…”
Section: Discussion Plant Mitochondrial Sss Is Controlled By At Leastmentioning
confidence: 71%
“…While both genes have maintained sequence features strongly reminiscent of their bacterial counterparts, several modifications have occurred in both genes that appear to be conserved in plants. We have described some of the distinguishing features of the RECA3 protein sequence in this study and recently reported novel features of MSH1, including well-conserved protein domains and an unusual fusion with a GIY-YIG endonuclease (Abdelnoor et al, 2006). Other essential recombination controls within the mitochondrial and plastid genomes appear to be performed by at least two additional recA homologs in Arabidopsis.…”
Section: Discussion Plant Mitochondrial Sss Is Controlled By At Leastmentioning
confidence: 71%
“…MSH1 is the mitochondrialtargeted MUTS homolog and MUTS homologs are generally involved in mismatch repair (84). While MSH4 and MSH5 have evolved distinct functions in meiosis (see above), MSH1, so far identified only in yeast and plants (not in vertebrates, nematodes, or insects), appears to have evolved a distinct function in mt genomes (85,86). The MSH1-like homologs identified herein were similar to the distinct plant MSH1 involved in "sub-stoichiometric shifting".…”
Section: ) Sexmentioning
confidence: 99%
“…In this study, we use the following naming of the MutS subfamilies, which is adapted from the recent study by Lin et al (Lin et al, 2007). In total, 12 subfamilies were previously described to compose the MutS family: 'MutS1/ MSH1' including E. coli MutS and the mitochondria-targeted fungal MutS homolog 1 (MSH1); 'MutS2', known to inhibit recombination in H. pylori (Pinto et al, 2005) and to possess a C-terminal endonuclease domain called the small MutS-related (Smr) domain (Moreira and Philippe, 1999;Fukui et al, 2008); 'MSH2', 'MSH3', 'MSH4', 'MSH5' and 'MSH6/7', found in most eukaryotes (with the exception of MSH7 being a plant-specific paralogous group of MSH6 (Wu et al, 2003)); another plantspecific MSH1 (called 'plt-MSH1' hereafter) with the GIY-YIG endonuclease domain at their C-terminus (Abdelnoor et al, 2006); 'MutS3', 'MutS4' and 'MutS5', recently described but functionally uncharacterized prokaryotic homologs (Lin et al, 2007), and the above mentioned 'MutS7' subfamily represented by the Mimivirus MutS homolog.…”
Section: Introductionmentioning
confidence: 99%